THE DEVELOPMENT OF EMPATHY SKILLS FOR GUIDANCE AND COUNSELING TEACHER CANDIDATES - Fanny Nishfiyati Iqlima; Nandang Budimann; Yusi Riksa Yustiana; Dodi Suryana (EDUCATIONE, 2026)
This study was motivated by the low personal quality of the counselor teachers resulting in the unwillingness of the counselee to consult. The purpose of the study was to show a description of the development of empathy skills possessed by prospective guidance and counseling teachers candidates. The participants in this study were 156 students of the Department of Educational Psychology and Guidance at the Faculty of Education, Universitas Pendidikan Indonesia. The data were collected through a self-report questionnaire to measure empathy. The results showed that the development of empathy was mostly in the medium category with a proportion of 35.25%, meaning that Guidance and Counseling Teacher candidates tend to be confused and hesitant to understand the views of others in a condition, sometimes unable to position themselves imaginatively towards fictional feelings and actions, lack feelings of warmth, affection, and care for the suffering of others, and sometimes unable to feel discomfort like others because of being influenced by several factors such as closeness and experience. The analysis of perspective-taking indicator was a low category; also, the development of female empathy was higher than that of men, so the empathy skills possessed by the Guidance and Counseling candidates had not to reach a holistic counselor personally.